T cell proliferation induced by monoclonal antibodies to a phosphatidylinositol-linked differentiation antigen of guinea pig lymphocytes - Schäfer, Hubert; Scheper, R. J.; Healey, D. G.; Schenkel, Johannes; Burger, Reinhard (European journal of immunology, 1991)
Monoclonal antibodies (mAb) to differentiation antigens frequently influence the in vitro function of antigen-bearing cells. We characterized a 32-36-kDa membrane protein expressed on guinea pig lymphocytes and Langerhans cells. A series of independently derived mAb to this protein, now called guinea pig T cell activation antigen (gpTAA), induced strong proliferation of T cells in vitro. Cross-linking of the mAb by a secondary antibody (rabbit anti-mouse Ig) and costimulation with phorbol 12-myristate 13-acetate were required for activation. Treatment of the cells with phosphatidylinositol-specific phospholipase C greatly reduced the amount of antigen expressed on the cell surface as measured by flow cytometry analysis. This finding indicates that the antigen is anchored to the cell membrane via phosphatidylinositol linkage as shown similarly for other membrane proteins with T cell activating properties, e.g. Thy-1 and Ly-6. The guinea pig protein differs, however, in its molecular weight and tissue distribution from similar proteins identified in the mouse or in the rat system. Unlike Thy-1, gpTAA is also expressed on B Lymphocytes and Langerhans cells. Considering the previously described involvement in cellular adhesion, and the functional characteristics reported here, gpTAA might represent a new species of differentiation antigen with T cell-activating capacity.
Gesehen am 05.03.2021